INTERAKSI DAN HUBUNGAN PARASOSIAL DALAM AKUN MEDIA SOSIAL SELEBRITI INDONESIA - Nuria Astagini; Veronica Kaihatu; Yugo Dwi Prasetyo (Communicology: Jurnal Ilmu Komunikasi, 2017)
Interaction and parasocial relationships are one-way relationships formed through the media. This type of relationship can be seen through various social media accounts owned by celebrities. Fans interactions with their idol celebrities in social media will lead to the formation of positive and negative parasocial relationships. This study was conducted to see how the relationship and parasocial relationship that exists between the fans with the celebrities in social media. Through observation on social media accounts owned by several celebrities in Indonesia, and in-depth interviews conducted with informants; It is known that various comments given by fans is a description of a parasocial interaction. Fans who always comments on every updated information uploaded by their idol, shows a parasocial relationship. This relationship is a picture of emotional attachment from the fans. The interaction and parasocial relationship in social media are closely related to the concept of hyperreality. All things related to a particular celebrity may be rendered artificially, so the fans will eventually form identification of the celebrity with hyperrealitas or reality that is different from the actual reality.